Formation mechanism and evaluation of geothermal resources in Yanqi Qikexing town, Xinjiang - Mengmeng Zhao; Kai Chen; Jinyu Chang; Genyi He; Feng Chen; Lifeng Chen; Zhiqi Liu; Yuhang Huang (Scientific Reports)
Abstract The study of geothermal genesis mechanism is the basis for the evaluation and effective development of geothermal field resources. On the basis of previous research results, the formation mechanism of geothermal field in Qikexing Township was analysed and the geothermal resources were evaluated by identifying geothermal anomalies in the area. In this paper, two geothermal anomalies were identified based on remote sensing inversion, soil chemical exploration, shallow temperature measurement and the main heat-control fractures, and the distribution characteristics and causes of hot springs were comprehensively studied by means of hydrogeochemistry and isotope analysis. The results show that the sources of geothermal water recharge are atmospheric precipitation and ice melt water in the vicinity. The cations of the geothermal water are mainly Na+, with an anionic ratio of 68.75%, followed by Ca2+ and K+; the anions are mainly SO4 2−, with an anionic ratio of 47.25%, followed by Cl− and HCO3 −; and the geothermal water is of the Cl·SO4-Na(Ca) type. The geothermal wells are mainly distributed along the active fracture spreading direction in the form of beads, and the maximum depth of thermal storage cycle is 2393 m. The temperature of thermal storage ranges from 49.4 to 93.7 ℃, and the heat source mainly comes from the heat transfer of mantle channel flow, the heat generated by the decay of radioactive elements, the heat generated by magmatic activities and so on. The results of the evaluation of geothermal resources in the study area show that the total geothermal resources are 1.38 × 1019 J/a, equivalent to 4.71 × 108 t/a of standard coal. This study mainly focuses on the distribution law of hydrothermal geothermal resources in Yanqi Qikexing town and the geothermal genesis, which can provide a reference basis for the development and utilisation of geothermal resources in Yanqi County in the later stage.